Amenable Argumentation Approach: Accommodating Emotional Arguments - Carozza, Linda (Informal Logic, 2022)
This paper summarizes various interpretations of emotional arguments, with a focus on the emotional mode of argument introduced in the multi-modal argumentation model (Gilbert, 1994). From there the author shifts from a descriptive account of emotional arguments to a discussion about a normative framework. Pointing out problems with evaluative models of the emotional mode, a paradigmatic shift captured by the Amenable Argumentation Approach is explained as a way forward for the advancement of the emotional mode and multi-modal argumentation.